A Unified Strategy for Sequence and Sequence-less T-way Test Suite Generation - Abdullah, Nasser; Hujainah, Fadhl; Alsewari, Abdulrahman A.; Kamal Z., Zamli (Faculty of Computer Systems & Software Engineering, Universiti Malaysia Pahang, 2016)
In the last 20 years, many useful t-way strategies (where t indicates the interaction strength) have been developed to help generate test suite for detecting fault due to interaction of inputs. Although useful, existing t-way strategies have assumed sequence-less interactions amongst input parameters. In the case of reactive system, such an assumption is invalid. This paper presents a unified strategy based on the new meta-heuristic algorithm, called the Elitist Flower Pollination Algorithm (eFPA), for sequence and sequence-less coverage. Experimental results demonstrate the proposed strategy gives sufficiently competitive results as compared with existing works.